WHEN FAITH MEETS FASHION: UNVEILING THE INFLUENCE OF HALAL SUPPLY CHAIN DIMENSIONS AND RELIGIOSITY ON HALAL FASHION INTENTIONS - Gina Destrianti Karmanto; Kurnia Sari Kasmiarno; Muhammad Anis; Yosi Mardoni (Ekonomi Islam, 2026)
Research aims: This study examines how halal supply chain awareness influences the purchase intention of halal fashion products among Indonesian Millennials and Generation Z, a key driver of Indonesia’s ambition to become a global halal hub. Design/Methodology/Approach: Grounded in the Theory of Reasoned Action and the Theory of Planned Behavior, this study integrates four dimensions of halal supply chain knowledge there is halal resourcing, halal handling and logistics, halal producing and design, and halal retailing with religiosity as a moderating variable. A mixed-method approach was applied, combining a survey of 221 respondents from Java Island, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), and in-depth interviews with academics and industry practitioners. Research findings: Halal resourcing, halal retailing, and religiosity significantly influence purchase intention, while halal handling and logistics, and halal producing and design show no significant effect. Religiosity has a direct positive effect but does not moderate the relationship between halal supply chain awareness and purchase intention. Qualitative insights highlight that consumer understanding of halal fashion remains limited, often confined to food-related contexts. Theoretical Contribution/Originality: This research is among the first to link halal supply chain awareness and religiosity to halal fashion purchase intention using a mixed-method design. Practitioners/Policy Implications: The study offers insights for policymakers and industry stakeholders to enhance public literacy and strengthen halal certification integrity within Indonesia’s halal fashion market Research Limitations/Implications:  This study is limited to Muslim respondents in West Java; therefore, future research may consider comparative analyses between Muslim and non-Muslim populations. In addition, the present study focuses solely on the consumer perspective, suggesting that future studies should incorporate the producer perspective to provide a more comprehensive understanding.